2012
DOI: 10.1371/journal.pone.0042993
|View full text |Cite
|
Sign up to set email alerts
|

Brain Networks of Explicit and Implicit Learning

Abstract: Are explicit versus implicit learning mechanisms reflected in the brain as distinct neural structures, as previous research indicates, or are they distinguished by brain networks that involve overlapping systems with differential connectivity? In this functional MRI study we examined the neural correlates of explicit and implicit learning of artificial grammar sequences. Using effective connectivity analyses we found that brain networks of different connectivity underlie the two types of learning: while both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
90
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 56 publications
8
90
0
1
Order By: Relevance
“…In a study of some 400 German schoolchildren, Gebauer and Mackintosh (2007) reported nonsignificant correlations ranging from .07 to .11 between different components of IQ and performance under incidental instructions, while under explicit instructions the now significant correlations ranged from .23 to .37. In a rather smaller study, Yang and Li (2012) observed a correlation of .56 between working memory and artificial grammar learning under explicit instructions, but no correlation under incidental instructions.…”
Section: Figure 4 About Here Pleasementioning
confidence: 73%
“…In a study of some 400 German schoolchildren, Gebauer and Mackintosh (2007) reported nonsignificant correlations ranging from .07 to .11 between different components of IQ and performance under incidental instructions, while under explicit instructions the now significant correlations ranged from .23 to .37. In a rather smaller study, Yang and Li (2012) observed a correlation of .56 between working memory and artificial grammar learning under explicit instructions, but no correlation under incidental instructions.…”
Section: Figure 4 About Here Pleasementioning
confidence: 73%
“…Data-driven approaches have recently been developed to enable researchers to examine both the activation and connection at a given time (contemporaneously) and their directions of influence across different times (sequentially). In particular, Gates, Molenaar, Hillary, Ram, and Rovine (2010) developed the unified structural equation modeling (uSEM) and the extended unified structural equation modeling (euSEM; see Methods for a description of uSEM and euSEM), which have allowed us to study brain networks of cognition and language (see two recent publications that have applied euSEM; Nichols, Gates, Molenaar, & Wilson, 2014;Yang & Li, 2012). In this study we will use both uSEM and euSEM to do effective connectivity analyses on our fMRI data, in order to show the dynamic interactions between key brain regions that subserve the learning of a second language vocabulary.…”
Section: Short-term L2 Training Studies: a Brief Reviewmentioning
confidence: 99%
“…The procedure for using the uSEM and euSEM is similar to that of Yang and Li (2012), but with the addition of the recently developed Group Iterative Multiple Model Estimation (GIMME; https://www. nitrc.org/projects/gimme/), an automatic, freely distributed MATLAB-based program (Mathworks, 2010: www.mathworks.com).…”
Section: Effective Connectivitymentioning
confidence: 99%
“…Hence we predict dynamic changes in resting-state activity over a six-h daytime consolidation period, and we tested this by comparing resting state activity at three time points after serial reaction time task (SRTT) learning. We hypothesize that SRTT learning under implicit conditions will initially engage sensory motor circuits (Wilkinson et al, 2010), and learning under explicit conditions will also engage prefrontal cortex (Grafton et al, 1995;Yang and Li, 2012).…”
Section: Introductionmentioning
confidence: 99%